To Assess the Antimicrobial Efficacy of Calendula officinalis in the Treatment of Gingivitis -A Randomized Controlled Trial - Radhika Muralidharan 21D03103; Dr Suman Basavaraju (JSS AHER, Mysuru JSSDC, Mysuru, 2024)
1. Introduction, 2.Objectives, 3.Literature Review,4.Methodology,5.Results,6.Discussion, 7.Conclusion,8.Summary, 9. References, 10.Annexures
Keywords: Periodontology